(3JaSjQ eJTGHI GdbQBfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3bhdg JYGdi (B: ( (3bO LGAce QShdfG jHjf dce Ydi aJQI (B) s
(3BNQgG (B:s
(3jfJgi HShQg Gdadb s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeY GdTjN GHQGgje HGTG (B(24) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs